SURVEI TENTANG KOMPETENSI GURU PENJASORKES DI SMP SE-KECAMATAN DUKUHSETI KABUPATEN PATI TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the competence of teachers penjasorkes in Junior High School - District of PATI Dukuhseti district in 2013. This study is a survey research, the sample used for this study using sampling techniques porposive. Of the 9 secondary school - District of Dukuhseti researchers chose three SMP ie SMP N 2 Dukuhseti, junior BOPKRI 3 Dukuhseti and Mts. Miftahul Falah. The data collection method used observation, questionnaires, documentation and interviews. To test the validity of using the product moment and relabilitasnya using the formula alpha test and data analysis techniques using data analysis techniques Diskriptif percentage. The results of this study showed that of the three sampled showed 34% excellent, 35% good, 22% and 9% less very less. Conclusion The results of this study are penjasorkes teachers competent enough, but there are some things that have not been controlled by the teacher so that the teacher penjasorkes penjasorkes must learn in order to be a true teacher - really competent.